Analysis of Tourist Sentiment towards Tourist Attractions in the Mandalika Special Economic Zone Using the NaÃ¯ve Bayes Method - Pribadi, Teguh Iman; Fahry, Fahry; Muharis, Muharis; Marswandi, Ega Dwi Putri (Jurnal Bumigora Information Technology (BITe), 2024)
The Mandalika Special Economic Zone has become one of the most popular destinations for both domestic and international tourists. This popularity highlights the importance of understanding the views and feelings of the tourists. Therefore, this study aims to analyze tourist sentiment towards the attractions in the Mandalika Special Economic Zone. The data analyzed was obtained from 1,144 reviews on the TripAdvisor platform. The research stages included data collection, data labeling, data preprocessing, data transformation, data classification, as well as data analysis and visualization. The results of this study indicate that the majority of tourists have a positive sentiment towards the attractions in the Mandalika Special Economic Zone. Furthermore, testing with the NaÃ¯ve Bayes algorithm successfully classified tourist sentiments accurately, with consistent accuracy rates obtained from each fold: fold 1: 89.08%, fold 2: 89.96%, fold 3: 88.21%, fold 4: 87.34%, and fold 5: 90.79%.